Stand structure and species diversity regulate biomass carbon stock under major Central Himalayan forest types of India - Kaushal, Siddhartha; Baishya, Ratul (Ecological processes, 2021)
Background Data on the impact of species diversity on biomass in the Central Himalayas, along with stand structural attributes is sparse and inconsistent. Moreover, few studies in the region have related population structure and the influence of large trees on biomass. Such data is crucial for maintaining Himalayan biodiversity and carbon stock. Therefore, we investigated these relationships in major Central Himalayan forest types using non-destructive methodologies to determine key factors and underlying mechanisms. Results Tropical Shorea robusta dominant forest has the highest total biomass density (1280.79 Mg ha −1 ) and total carbon density (577.77 Mg C ha −1 ) along with the highest total species richness (21 species). The stem density ranged between 153 and 457 trees ha −1 with large trees (> 70 cm diameter) contributing 0–22%. Conifer dominant forest types had higher median diameter and Cedrus deodara forest had the highest growing stock (718.87 m 3 ha −1 ); furthermore, C . deodara contributed maximally toward total carbon density (14.6%) among all the 53 species combined. Quercus semecarpifolia – Rhododendron arboreum association forest had the highest total basal area (94.75 m 2 ha −1 ). We found large trees to contribute up to 65% of the growing stock. Nine percent of the species contributed more than 50% of the carbon stock. Species dominance regulated the growing stock significantly ( R 2 = 0.707, p < 0.001). Temperate forest types had heterogeneous biomass distribution within the forest stands. We found total basal area, large tree density, maximum diameter, species richness, and species diversity as the predominant variables with a significant positive influence on biomass carbon stock. Both structural attributes and diversity influenced the ordination of study sites under PCA analysis. Elevation showed no significant correlation with either biomass or species diversity components. Conclusions The results suggest biomass hyperdominance with both selection effects and niche complementarity to play a complex mechanism in enhancing Central Himalayan biomass carbon stock. Major climax forests are in an alarming state regarding future carbon security. Large trees and selective species act as key regulators of biomass stocks; however, species diversity also has a positive influence and should also reflect under management implications.